HOST CYTOKINE GENE POLYMORPHISMS AND PARASITE GENETIC VARIABILITY IN DETERMINING THE DISEASE OUTCOME OF Plasmodium falciparum INFECTION (2012)
Malaria, the world’s most important tropical parasitic disease is caused by Plasmodium species. Infection with Plasmodium falciparum can result in one of three possible disease outcomes: Asymptomatic (AS), Uncomplicated Malaria (UM) or Severe Malaria (SM). Information on host genetic factors and parasite genetic diversity can improve understanding of the disease pathogenesis. In this study, the genetic diversity of P. falciparum isolates as well as polymorphisms in host cytokine genes was investigated in relation to the outcome of P. falciparum infection. Four hundred and thirty-seven children recruited from the Specialist Hospital, Lafia, Nasarawa State were assigned into UM or SM based on malaria severity, determined by clinical and laboratory diagnoses. Asymptomatic children recruited from primary schools within the study location constituted the control group (AS). Plasmodium falciparum infection was confirmed by PCR-based assay of SSUrRNA genes. Genetic diversity of P. falciparum was analyzed by genotyping the polymorphic domains of the Merozoite Surface Protein 2 (MSP-2). Host cytokine genes investigated included Interleukin-18 (IL-18), IL-18 receptor alpha (IL-18Rα) and Tumour Necrosis Factor alpha (TNF-α). Sequencing of MSP-2 gene and of the pro-inflammatory cytokines was carried out using ABI PRISM® 3100. Sequences were analyzed using the BioEdit Sequence Alignment software. Genotype and allelic frequencies were analyzed by Chi-square test. The level of significance was set at P=0.05. All participants had P. falciparum infection. Polyclonality was significantly higher in the AS (61%) and UM (60%) groups compared with the SM (34%) group. Mean multiple infections was 2.1 ±1.0 in AS, 2.0 ±1.0 in UM and 1.3 ±0.6 in SM. A total of 32, 35 and 28 distinct MSP-2 alleles were found in the AS, UM and SM groups respectively. Frequency of the 3D7 allele type was significantly higher in UM (51%) and SM (54%) groups compared to the AS group (38%). Sequence analysis of the central variable region of the MSP-2 gene showed that the FC27-type sequence was characterised by two unique subtypes and hybrid sharing sequence with the two subtypes. The 3D7-type sequence was characterised by three subtypes of repetitive domains: a GSA-rich repeat unit, a TPA repeat motif and a poly-Threonine stretch. Three single nucleotide polymorphisms (SNPs): -656G/T, -607C/A and -137G/C were identified at the promoter region of IL-18 gene. The -656G/T and -607C/A SNPs were found to be in complete linkage disequilibrium. The genotype frequency of -607AA was significantly higher in the AS group compared to SM cases (χ2=4.26, P<0.05). Likewise, four SNPs were identified at the promoter and Exon 1 of the IL-18Rα: -661T/C, -175G/A, -93C/T and Ex1 +21C/G but none was associated with disease outcome based on statistical level of significance. Exons 2 to 11 of IL-18Rα gene were relatively conserved. Furthermore, two SNPs: -308G/A and -238G/A were identified at the promoter region of TNF-α but none was associated with disease outcome. Plasmodium falciparum was found to be genetically heterogeneous. Higher carriage of Plasmodium falciparum 3D7 alleles indicates higher risk of developing symptomatic malaria. There was association between IL18 -607AA genotype and asymptomatic infection, probably indicating a protective role.